Additional Validity Evidence and Across-Group Equivalency of the HOPE Teacher Rating Scale. (April 2013) - Peters, Scott J.; Gentry, Marcia
The HOPE Scale was developed to identify academic and social components of giftedness and talent in elementary-aged students with particular attention to students from low-income and/or culturally diverse families. Based on previous findings, additional research was conducted on revisions made to the HOPE Scale . Items were added, and 71 teachers completed the HOPE Scale on 1, 700 diverse students. The HOPE Scale was evaluated for differential item and test functioning with regard to gender, ethnic/racial, and income groups. Differential item functioning was not found with ethnic/racial or income group membership, but it existed for gender. HOPE Scale scores were also compared with achievement test scores to contribute criterion-related validity information. Results indicate that HOPE Scale scores account for approximately 52% to 58% of achievement test scores.